Predictors of Company Value in the Property and Real Estate Sector on the Indonesian Stock Exchange for the Period 2022–2024 - Sanjaya Sjim, Felicia; Siswanto, Halim Putera (Jurnal Indonesia Sosial Sains, 2026)
The property and real estate sector plays a strategic role in the Indonesian economy; however, it faces challenges related to capital intensity, market volatility, and fluctuating firm valuations, as reflected in the instability of Price-to-Book Value (PBV) in recent years. These conditions highlight the importance of understanding the key financial factors that influence firm value, particularly leverage, profitability, and firm size, which are often used by investors to assess company performance and risk. This research examines the influence of leverage, profitability, and firm size on firm value among property and real estate companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. The study applies a quantitative approach using secondary data derived from annual financial reports and employs a purposive sampling technique, yielding 39 firms and 117 observations. Data analysis is conducted using multiple linear regression to identify the effects of independent variables on firm value. The results indicate that leverage has a significant negative effect, profitability has no significant effect, and firm size has a significant negative effect on firm value. These findings suggest that the market responds more cautiously to higher debt levels and larger firm size, while profitability has yet to become the most determining factor in investor assessments during the observation period.